2014
DOI: 10.1063/1.4866293
|View full text |Cite
|
Sign up to set email alerts
|

Activation and deactivation of vibronic channels in intact phycocyanin rods

Abstract: We investigated the excitation modes of the light-harvesting protein phycocyanin (PC) from Thermosynechococcus vulcanus in the crystalline state using UV and near-infrared Raman spectroscopy. The spectra revealed the absence of a hydrogen out-of-plane wagging (HOOP) mode in the PC trimer, which suggests that the HOOP mode is activated in the intact PC rod, while it is not active in the PC trimer. Furthermore, in the PC trimer an intense mode at 984 cm(-1) is assigned to the C-C stretching vibration while the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Our observations fit well with the activation and deactivation of HOOP wagging, CvC stretching, and the N-H rocking in-plane vibration. 21 We also observed strong localized vibronic coupling between β 84 in adjacent PC trimers in the PC rod of A. marina. 9 In the hexameric PC assembly, Womick et al recently showed that the fastest EET component is 970 fs, 18 while, in a fragment of PC bound to APC, Sandström et al found 17 ps and 50 ps kinetic components.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Our observations fit well with the activation and deactivation of HOOP wagging, CvC stretching, and the N-H rocking in-plane vibration. 21 We also observed strong localized vibronic coupling between β 84 in adjacent PC trimers in the PC rod of A. marina. 9 In the hexameric PC assembly, Womick et al recently showed that the fastest EET component is 970 fs, 18 while, in a fragment of PC bound to APC, Sandström et al found 17 ps and 50 ps kinetic components.…”
Section: Introductionmentioning
confidence: 53%
“…There are two different states not located in the last heterohexamer, which some have suggested is the terminal emitter of the PBS in A. marina. 21 Since the APC trimer already forms an excitonic absorption state at 645 nm, there is no more evidence of further localized APC trimer excitonic state. Therefore, the origin of the terminal emitter, or its pigment composition, remains an open issue.…”
Section: Photochemical and Photobiological Sciences Papermentioning
confidence: 99%
See 2 more Smart Citations
“…The translation stage of 1 ns and the Lock-In amplifier were controlled by a computer, which was also used for data acquisition. The details and illustration of the set-up has been outlined by Nganou et al 33…”
Section: Femtosecond Pump-probe Transient Absorption Spectroscopymentioning
confidence: 99%